An investigation of the impact of formal and informal assessment on the self-esteem of pupils with borderline learning difficulties learning in mixed ability English language classes - Ndebele, Kordwick (2009)
This thesis reports on a research study aimed at examining the impact of informal and formal assessment on the self-esteem of pupils with borderline difficulties and language deficiencies learning in mixed ability English language classes. The thesis adopted a qualitative ethnographic methodology with triangulated methods to enquire into macro and micro views of the main concepts in this study. Thus, data were collected by participant observation within English classes, informal and formal interviews with pupils and teachers at the research site and semi-structured interviews at home with parents and pupils. Questionnaires for 6 teachers, pupils and parents [total n=31] were administered 22 pupils were observed over a period of nine months, spanning 5th September 2005 to May 2006 and 3 parents interviewed due to availability of willing pupils and their parents. This was followed by structured and semi-structured questionnaire administration and interviews with six teachers and pupils [n=22].